The religious worldviews reflected in the Dead Sea Scrolls: proceedings of the fourteenth international symposium of the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature, 28-30 May, 2013 - Clements, Ruth E.; Ḳisṭer, Menaḥem; Segal, Michael; Clements, Ruth (Studies on the texts of the desert of Judah, 2018)
"The Dead Sea Scrolls offer a window onto the rich theological landscape of Judaism in the Second Temple period. Through careful textual analysis, the authors of these twelve studies explore such topics as dualism and determinism, esoteric knowledge, eschatology and covenant, the nature of heaven and/or the divine, moral agency, and more; as well as connections between concepts expressed in the Qumran corpus and in later Jewish and Christian literature. The religious worldviews reflected in the Scrolls constitute part of the ideological environment of Second Temple Judaism; the analysis of these texts is essential for the reconstruction of that milieu. Taken together, these studies indicate the breadth and depth of theological reflection in the Second Temple period"--